Re-Constructing Identity Between Place and Space: The Case of Highly Skilled EU Migrants to Bucharest - Voicu, Bogdan; Deliu, Alexandra (Calitatea Vieții, 2024)
Approaching identity in a constructivist manner (Weigert et al. 1986), we conceive of it as embedded in social interactions with people and collectivities and consider international migration as a vehicle to change such contexts (Dinesen 2013). Therefore, we explore identity transformations in international migrants, focusing on the case of highly skilled EU immigrants to Bucharest. The place is peculiar as a wealthy enclave in the poorest region in the European Union. Our target immigrants may be atypical, but they have the advantage of being able to better control and influence their context (Favell 2008). We document a subtle process of change in reference to self-definitions and evaluations of alterity. Through analysing interviews with high-skilled immigrants (HSI) in Bucharest, we discuss the places of agency and structure in the self-definitions of migrants. We argue that structural elements are filtered by the direct experiences of HSIs, while their agency and personal characteristics make them less exposed to constraints of any kind. At the same time, we contend that interactions at the destination contribute to the redefinition of original expectations and plans. Homemaking strategies act as a substitute for maintaining the identity shaped by the culture of origin.